Racial diversity and its asymmetry within and across hierarchical levels: The effects on financial performance. (October 2019) - Smulowitz, Stephen; Becerra, Manuel; Mayo, Margarita
The benefits and drawbacks of diversity inside organizations have been the focus of attention for researchers and practitioners for several decades. In our article, we investigate the business case for racial diversity across different hierarchical levels. More precisely, we ask: How does racial diversity within organizations and its asymmetry across hierarchical levels affect their financial performance? From a sample of 143 US law firms from 2008 to 2012, we provide strong support for the business case and show that greater racial diversity for the entire organization is positively associated with firm financial performance. However, contrary to our initial expectations, the benefits of diversity are not more pronounced at the top of the organization, where its effects should arguably be more clearly observable. Diversity seems to have a similar effect across the three levels in law firms: associates, mid-level and partners. Furthermore, we find that the most profitable firms actually have their racial diversity heavily concentrated at the associate level. We discuss alternative explanations for this surprising finding and why the top-performing law firms have both overall higher degree of racial diversity and more concentration of its diversity at the lower level.